Computational insights of double perovskite Na2CaCdH6 hydride alloy for hydrogen storage applications: a DFT investigation - Muhammad Khuram Shahzad; Shoukat Hussain; Muhammad Noman Khan; Muhammad Jehanzaib Aslam; Rawaa M. Mohammed; Vineet Tirth; Hassan Alqahtani; Ali Algahtani; Tawfiq Al-Mughanam; Waqar Azeem (Scientific Reports, 2024)
Abstract Prospective use of perovskite hydride materials in H storage a crucial element of clean energy systems has drawn a lot of attention. The structural, electrical, mechanical, thermodynamic, and H storage qualities of Na2CaCdH6 hydride alloys were examined in this work using DFT. According to the structural properties, Na2CaCdH6 has space group 225 (Fm3m), and optimized lattice parameters and volume of Na2CaCdH6 are 3.3485 Å and 593.764 Å3. The measured gravimetric H storage capacity of Na2CaCdH6 hydrides is 2.956 wt%. The hydrides under research are semiconductors, as indicated by the computed electronic characteristics. Elastic constants, Pugh’s ratio, modulus, Poisson’s ratio, anisotropic, and microhardness of Na2CaCdH6 are calculated under mechanical properties. The hydrides are dynamically stable, as indicated by the phonon dispersion curves, but mechanically stable according to the Born criterion for elastic constant (Cij). The Cauchy’s pressure (C″ = 7.836) revealed the ductile behavior. The electronic and mechanical characteristics imply that Na2CaCdH6 hydride can conduct electricity and is also mechanically stable. Our findings shed light on the possibilities of Na2CaCdH6 perovskite hydride material for H storage utilization.